Doping Fe and Zn to modulate Ni nanoparticles on IM-5 for methane decomposition to form hydrogen and CNTs. (26th April 2023) - Sun, Huayang; Ren, Shenyong; Ji, Xiangyang; Song, Weiyu; Guo, Qiaoxia; Shen, Baojian
Abstract: Catalysts Ni/IM-5 doped with Fe and/or Zn were studied to promote the performance in the catalytic decomposition of methane (CDM) to simultaneously produce hydrogen and carbon nanotubes (CNTs). The catalyst Ni20 Fe5 Zn5 /IM-5 showed high methane conversion (c.a. 65%) and 100% selectivity towards H2 in 300 min at 670 °C. In the Fe atoms inhibited the formation of larger Ni particles. Zn atoms enhanced the migration of C atoms over the surface of the catalyst. IM-5 was speculated to provide better diffusion of C atoms to avoid the excessive deposition of carbon. The synergistic effect between metal and IM-5 enabled the catalyst to selectively produce pure and high graphitization CNTs. A carbon migration model was proposed to explain the synergistic effect between metals and zeolite. The atom erosion as dominant reason of catalyst deactivation was confirmed by XRD and TEM. According to density functional theory (DFT), bimetallic Fe and Zn promoter catalyst was more favorable for the initial bond cleavage of CH4 . Graphical abstract: Image 1 Highlights: Catalysts Ni/IM-5 doped with Fe and/or Zn were prepared for decomposition of methane to produce hydrogen and CNTs. Catalyst Ni20 Fe5 Zn5 /IM-5 showed high methane conversion (c.a. 65%) and 100% selectivity towards H2 in 300 min at 670 °C. The synergistic effect between metal and IM-5 enabled the catalyst to selectively produce pure and highly graphitized CNTs. A possible growth mechanism of the CNTs and the diffusion of carbon atoms in the pore of IM-5 were discussed.